1984
DOI: 10.2307/1941399
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Budgets and Internal Cycling of N, P, K, Ca, and Mg in Conventional Tillage, No‐Tillage, and Old‐Field Ecosystems on the Georgia Piedmont

Abstract: Nutrient budgets (N, P, K, Ca, and Mg) were developed for conventional—tillage, no—tillage, and old—field systems. Data for the budgets were collected over a 2—yr period, with grain sorghum as a main season crop followed by a cover crop of winter rye. Nutrient uptake by crops, weeds, and old—field plants was the largest flow in each system. Leaching losses were small compared to input from fertilizer (except for Ca). Leaching losses of N and Ca was greatest in conventional—tillage, followed by no—tillage syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…) showed that the simulated rates were close to the observed rates (Table 4). Comparison of the simulated N mineralization rates in the HSB webs with estimates of N mineralization rates obtained from N budget analyses (Stinner et al, 1984) showed that the simulated N mineralization rates were higher than the rates obtained from the N budgets. It must however be noted that the estimates obtained from the N budgets differed strongly between years (Table 4), and that the data used for the present simulation were from different years (1983)(1984) than the data used for the N budgets (1978)(1979)(1980).…”
Section: Comparison With Other Estimates Of C and N Mineralizationmentioning
confidence: 81%
See 1 more Smart Citation
“…) showed that the simulated rates were close to the observed rates (Table 4). Comparison of the simulated N mineralization rates in the HSB webs with estimates of N mineralization rates obtained from N budget analyses (Stinner et al, 1984) showed that the simulated N mineralization rates were higher than the rates obtained from the N budgets. It must however be noted that the estimates obtained from the N budgets differed strongly between years (Table 4), and that the data used for the present simulation were from different years (1983)(1984) than the data used for the N budgets (1978)(1979)(1980).…”
Section: Comparison With Other Estimates Of C and N Mineralizationmentioning
confidence: 81%
“…a Obtained from in situ measurements (Bloem et al, 1994). b Obtained from a N budget for 1978/1979 (Stinner et al, 1984). c Obtained from a N budget for 1979/1980 (Stinner et al, 1984).…”
Section: Comparison With Other Estimates Of C and N Mineralizationmentioning
confidence: 99%
“…This site is located on a river floodplain on Hiwassee series soil (fine loamy, siliceous, thermic, and Rhodic Kanhapludult). Clover and rye have been the winter cover crops in the plots since 1978 (3,30,31,72). Maize (Zea mays L.) was the summer crop in 1996 and 1997.…”
Section: Methodsmentioning
confidence: 99%
“…The HSB site is about 14 ha in area and is surrounded on three sides by a meander loop of the North Oconee River. Except for the cropped areas and perimeter, which is forested, much of the site is in successional old field vegetation [Stinner et al, 1984]. The soil is a well-drained sandy-clay loam (66% sand, 13% silt, and 21% clay in the row crops area [Groffman et al, 1986]) with moderately high fertility relative to the southern Piedmont [Stinner et al, 1984].…”
Section: Study Areamentioning
confidence: 99%
“…Except for the cropped areas and perimeter, which is forested, much of the site is in successional old field vegetation [Stinner et al, 1984]. The soil is a well-drained sandy-clay loam (66% sand, 13% silt, and 21% clay in the row crops area [Groffman et al, 1986]) with moderately high fertility relative to the southern Piedmont [Stinner et al, 1984]. The climate of the region is humid subtropical, with a mean annual temperature over the last 30 years of 16.3øC (25.5øC in summer and 6.7øC in winter [Hendrix, 1997]).…”
Section: Study Areamentioning
confidence: 99%